Komponen Pariwisata 4a (Attraction, Accessibility, Amenities, Ancillary) Di Daya Tarik Wisata Bali Zoo Kabupaten Gianyar, Bali - Anargya, I Gede Kanaka Ghali; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i02.p01, 2024)
Bali Zoo is a zoo that was founder in 2002 and became the first in Bali. This zoo is also one of the best zoo in Asia Pacific. With the familiarity of Bali Zoo, it is hoped that it will provide opportunities for the community to take advantage of existing potentials to support the sustainability of tourism activities. The purpose of this research is to analyse how tourism development in Bali Zoo uses 4A components, namely Attraction, Accessibility, Amenities, Ancillary. The research method uses a qualitative descriptive approach. The technique of determining informa using Purposive Sampling technique. Data collection techniques using interviews, observation, documentation, and literature studies. Keywords: Components, Tourism Development, Zoo.